2022
DOI: 10.2340/17453674.2022.2528
|View full text |Cite
|
Sign up to set email alerts
|

Precision of low-dose CT-based micromotion analysis technique for the assessment of early acetabular cup migration compared with gold standard RSA: a prospective study of 30 patients up to 1 year

Abstract: Background and purpose: Computed tomography micromotion analysis (CTMA) can be used to determine implant micro-movements using low-dose CT scans. By using CTMA, a non-invasive measurement of joint implant movement is enabled. We evaluated the precision of CTMA in measuring early cup migration. Standard marker-based radiostereometric analysis (RSA) was used as reference. We hypothesised that CTMA can be used as an alternative to RSA in assessing implant micromotions.Patients and methods: We included 30 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…Reported precisions (when defined as 1.96 × SD) for traditional and model-based RSA in comparable acetabular cup configurations range from 0.01 to 0.29 mm for translations and from 0.05° to 0.59° for rotations. 9 , 10 , 12 , 13 Reported precisions for CT-based migration analysis techniques in acetabular cups range from 0.03 to 0.16 mm for translations and from 0.06° to 0.37° for rotations. 9 , 10 , 12 The method presented in this paper shows comparable acetabular cup precision to these methods of 0.08–0.11 mm for translations and 0.19°–0.42° for rotations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Reported precisions (when defined as 1.96 × SD) for traditional and model-based RSA in comparable acetabular cup configurations range from 0.01 to 0.29 mm for translations and from 0.05° to 0.59° for rotations. 9 , 10 , 12 , 13 Reported precisions for CT-based migration analysis techniques in acetabular cups range from 0.03 to 0.16 mm for translations and from 0.06° to 0.37° for rotations. 9 , 10 , 12 The method presented in this paper shows comparable acetabular cup precision to these methods of 0.08–0.11 mm for translations and 0.19°–0.42° for rotations.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 , 12 , 13 Reported precisions for CT-based migration analysis techniques in acetabular cups range from 0.03 to 0.16 mm for translations and from 0.06° to 0.37° for rotations. 9 , 10 , 12 The method presented in this paper shows comparable acetabular cup precision to these methods of 0.08–0.11 mm for translations and 0.19°–0.42° for rotations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Computed tomography (CT) offers direct 3-dimensional data that can serve as a substitute for traditional markers [12]. Preliminary arthroplasty studies with CT-based surface registration have shown comparable results to marker-based RSA without significant loss of accuracy or precision [13][14][15][16]. With respect to arthrokinematic studies, CTbased radiostereometry (CT-RSA) is not dependent on tantalum markers and, with surface detection, it could offer an alternative method for precision evaluation.…”
mentioning
confidence: 99%